2015
DOI: 10.1007/s10964-015-0341-x
|View full text |Cite
|
Sign up to set email alerts
|

How Do My Friends Matter? Examining Latino Adolescents’ Friendships, School Belonging, and Academic Achievement

Abstract: Are Latino adolescents' friendships an untapped resource for academic achievement or perhaps one of the reasons why these youth struggle academically? Using data from the National Longitudinal Study of Adolescent Health (N = 6782; 7th through 12th graders; 52.9 % female), we examined whether the process of Latino students' school belonging mediated the relationships between the context of friendships (i.e., friendship network indicators) and their academic outcomes (i.e., a context-process-outcomes model), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 45 publications
3
47
0
3
Order By: Relevance
“…Their findings show that low levels of social relationships have long-term negative effects on school performance and explain around 25% of school performance. Along the same line, Delgado et al (2016) carry out an analysis focusing on Latin American adolescents living in the US. Using a Structural Equation Model, they find that having close friends increases the sense of school belonging, this having in turn a positive effect on school attainment.…”
Section: The Empirical Evidence On the Role Of The Relationship With mentioning
confidence: 99%
“…Their findings show that low levels of social relationships have long-term negative effects on school performance and explain around 25% of school performance. Along the same line, Delgado et al (2016) carry out an analysis focusing on Latin American adolescents living in the US. Using a Structural Equation Model, they find that having close friends increases the sense of school belonging, this having in turn a positive effect on school attainment.…”
Section: The Empirical Evidence On the Role Of The Relationship With mentioning
confidence: 99%
“…Youths' educational expectation trajectories did not differ for African American, Native American, European American, or Hispanic youths. However, these studies focus on Hispanic youth as a monolithic group, ignoring the unique histories, social expectations, and educational experiences of Hispanic youth from different countries of origin (Delgado, Ettekal, Simpkins, & Schaefer, 2016; Portes & Rumbaut, 2006). Only one study has focused on Mexican-origin youth (Bravo, Toomey, Umaña-Taylor, Updegraff, & Jahromi, 2015); however, this study used data from adolescent mothers beginning in the third trimester of pregnancy and extended for three years.…”
Section: Trajectories Of Educational Expectationsmentioning
confidence: 99%
“…For example, a recent study analyzing U.S. Census statistics from 1960 to 2010 reported that Cuban Americans consistently outperformed Mexican and Puerto Rican students on the percentage of high school graduates (Ortiz, Valerio, & Lopez, ). Recent literature relevant to school belonging suggests that friendships are especially protective for the school belonging of Mexican‐origin adolescents compared with South or Central American youth (Delgado, Ettekal, Simpkins, & Schaefer, ). These researchers speculated that this difference may have occurred as a result of Mexican students being the numerically largest group and therefore more scrutinized, marginalized, and targeted for discrimination.…”
Section: The Current Studymentioning
confidence: 99%